The Andean genus Myrosmodes (Orchidaceae, Cranichideae) in Peru - Trujillo, Delsy; Gonzáles, Paúl; Trinidad, Huber; Cano, Asunción (Lankesteriana: International Journal on Orchidology, 2016)
A revision of Myrosmodes from Peru is presented. Seven species are recognized for the country. Each species is described and illustrated on the basis of a revision of type material, protologues and Peruvian specimens. Its distribution within the country is assessed. Myrosmodes nervosa is recorded for first time in Peru. New synonyms are proposed: M. cleefii is included under M. nubigena, M. inaequalis and M. pumilio under M. paludosa, M. weberbaueri under M. gymnandra, and M. cochlearis under M. rhynchocarpa. A key to identify the seven recognized species is also provided. A lectotype is designated for Aa chiogena.